The Effect Of Tax Avoidance, Company Size And Assets Structure On Capital Structure With Return On Equity As A Mediation Variable In Public Soe Companies Listed On Idx Period 2017-2021 - Trinita, Trinita; Ria Ginting, Rasinta; Adam Afiezan, H.; RSA, RSA; CJAT, CJAT (CV. Inara, 2022)
This study aims to examine and analyze the effect of Tax Avoidance, Company Size and Asset Structure on Capital Structure with Return On Equity as a mediating variable in public BUMN companies listed on the IDX for the period 2017 - 2021. This study is a quantitative study with the documentation method. The population of this research is state-owned companies that go public listed on the Indonesia Stock Exchange during the 2020 period, totaling 15 companies. The sample of this research is 12 companies selected by purposive sampling technique. Data analysis used path analysis with SPSS as the analysis tool. The results show that 1) Tax Avoidance has a negative effect on Return On Equity, 2) Firm Size has a positive effect on Return On Equity, 3) Asset Structure has no effect on Return On Equity, 4) Tax Avoidance has no effect on Capital Structure, 5) Size Companies have a positive effect on Capital Structure, 6) Asset Structure has no effect on Capital Structure, 7) Return On Equity has no effect on Capital Structure, 8) Return On Equity as an intervening variable is not able to significantly mediate Tax Avoidance on Capital Structure, 9) Return On Equity as an intervening variable is not able to significantly mediate Firm Size on Capital Structure and 10) Return On Equity as an intervening variable is not able to significantly mediate Asset Structure on Capital Structure.